Human-animal interactions in dairy production - Lundvall, Josefine; Saras-Johansson, Maria (SLU/Dept. of Animal Nutrition and Management (until 231231), 2011)
It has been clearly shown that welfare and productivity of animals is affected by the human-animal interaction. Despite the fact that the human-animal interaction is decreasing in a modern dairy production there will always be an interaction between humans and cattle. The key feature in a high performing dairy production of today is a positive human-animal interaction and therefore avoiding fear against humans. Fear causes stress which leads to a decreased milk yield and possibly to a decreased content of fat and protein. Due to the various results in earlier studies, more work need to be done determining how the human contact affects the productivity of the dairy cows. This is important since the dairy farmer get paid, not only by the yield, but also based upon the composition of the milk.